2015
DOI: 10.1589/jpts.27.3825
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fathers’ parenting participation with disabled children on parenting stress in mothers

Abstract: [Purpose] The purpose of this research was two-fold: (1) to evaluate the effects of father’s parenting participation on parenting stress among mothers with disabled children and (2) more specifically, to investigate the importance of fathers’ parenting participation in decreasing mothers’ parenting stress. [Subjects and Methods] To examine these relationships, this study recruited 82 mothers with disabled children from rehabilitation centers in the Gwangju city. The common characteristics of parents and childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
(13 reference statements)
0
11
0
2
Order By: Relevance
“…Çalışmamızda otizm, down sendromu, özel öğrenme güçlüğü, konuşma yetersizliği, yaygın gelişimsel bozukluk, dikkat eksikliği ve hiperaktivite bozukluğu, davranış bozukluğu, işitme yetersizliği ve fiziksel yetersizlik tanılı çocuklar özel gereksinimi olan çocuklar olarak belirlenmiştir. Özel gereksinimi olan çocuğa sahip ebeveynlerin yaşadıkları duygular incelendiğinde; belirsizlik, kaygı, umutsuzluk, çaresizlik, suçluluk, acıma, şok, yalnızlık ve öfkenin ön planda olduğu görülmektedir (5,8,30) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Çalışmamızda otizm, down sendromu, özel öğrenme güçlüğü, konuşma yetersizliği, yaygın gelişimsel bozukluk, dikkat eksikliği ve hiperaktivite bozukluğu, davranış bozukluğu, işitme yetersizliği ve fiziksel yetersizlik tanılı çocuklar özel gereksinimi olan çocuklar olarak belirlenmiştir. Özel gereksinimi olan çocuğa sahip ebeveynlerin yaşadıkları duygular incelendiğinde; belirsizlik, kaygı, umutsuzluk, çaresizlik, suçluluk, acıma, şok, yalnızlık ve öfkenin ön planda olduğu görülmektedir (5,8,30) .…”
Section: Discussionunclassified
“…Aileler, dünyaya gelen bebeğin engelli olması durumuna hazırlıklı değildir. Bu nedenle çocuğun doğumuyla yaşanacak olan mutluluk ve sevinç duygusu yerini yoğun bir üzüntü ve endişeye bırakır (5)(6)(7)(8) . Yapılan çalışmalara göre, engelli çocuk yetiştirmek aileler için sağlıklı çocuk yetiştirmeye oranla daha fazla stres tepkisine ve psikolojik rahatsızlıklara neden olmaktadır (9)(10)(11)(12) .…”
Section: Introductionunclassified
“…When the literature was taken into consideration, it was observed that the protection of families increased as the age of the disabled child with care was reduced and it was reported that this caused stress increase (Malm-Buatsi et al, 2015) and that mothers caring for disabled children in the long term were more stressed (Song et al, 2015). In this study, it was found that 46.2% of the parents who gave care to the disabled child received care support from their family or institution (Table 1).…”
Section: Discussionmentioning
confidence: 72%
“…It was found in this study that, 46.2% of the parents needed support to provide care for their disabled children and 41.5% of them required psychological support. Song et al stated that supporting the mother, who has a disabled child, in the care, household, play and leisure activities will reduce the stress level of the mother (Song et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation